Sistem Informasi Pengelolaan Kegiatan Masjid Raya Taqwa Palembang Berbasis Website Menggunakan Metode Agile - Melani, Afreti; Ariati, Nining; Kholik, Abdul (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
In today’s digital era, technological advancements have brought significant changes across various aspects of life, including the management of places of worship. This study aims to develop a web-based information system for managing the activities of the Taqwa Grand Mosque in Palembang. The system is designed to address the challenges of manual record-keeping, which is prone to errors, lacks transparency, and faces difficulties in reporting mosque funds and activities.This research employs the Agile methodology, which involves iterative stages such as planning, design, implementation, testing, and continuous evaluation. The information system includes features for managing infaq, zakat, and qurban funds online, scheduling mosque activities, and ensuring transparent financial reporting. The expected outcome is the creation of an integrated system that simplifies the management of mosque funds and activities, provides easy access for worshippers to donate digitally, and delivers accurate financial reports. This system also supports real-time information management, enhances operational efficiency, and builds the trust of worshippers in mosque management. With the application of this technology, it is hoped that the management of the Taqwa Grand Mosque can become more transparent.